Tributyltin Oxide Exposure During in vitro Maturation Disrupts Oocyte Maturation and Subsequent Embryonic Developmental Competence in Pigs - Xiao, Yue; Yuan, Bao; Hu, Weiyi; Qi, Jiajia; Jiang, Hao; Sun, Boxing; Zhang, Jiabao; Liang, Shuang (Frontiers in Cell and Developmental Biology, 2021)
Tributyltin oxide (TBTO), an organotin compound, has been demonstrated to have toxic effects on several cell types. Previous research has shown that TBTO impairs mouse denuded oocyte maturation. However, limited information is available on the effects of TBTO exposure on livestock reproductive systems, especially on porcine oocytes in the presence of dense cumulus cells. In the present research, we evaluated the effects of TBTO exposure on porcine oocyte maturation and the possible underlying mechanisms. Porcine cumulus-oocyte complexes were cultured in maturation medium with or without TBTO for 42 h. We found that TBTO exposure during oocyte maturation prevented polar body extrusion, inhibited cumulus expansion and impaired subsequent blastocyst formation after parthenogenetic activation. Further analysis revealed that TBTO exposure not only induced intracellular reactive oxygen species (ROS) accumulation but also caused a loss of mitochondrial membrane potential and reduced intracellular ATP generation. In addition, TBTO exposure impaired porcine oocyte quality by disrupting cellular iron homeostasis. Taken together, these results demonstrate that TBTO exposure impairs the porcine oocyte maturation process by inducing intracellular ROS accumulation, causing mitochondrial dysfunction, and disrupting cellular iron homeostasis, thus decreasing the quality and impairing the subsequent embryonic developmental competence of porcine oocytes.